Narrativization of Trauma as Performance in Modiain - Regmi, Laxmi (Humanities and Social Sciences Journal, 2023)
This study scrutinizes and analyzes Mahabharata War from the perspective of performance studies. The text chosen for analysis is a seminal work of Bishweshwor Prasad Koirala as a satire against war, Modiain. The paper intends to show the violence, futility of war, enormous pain, fear, estrangement, unhappiness and shadow of war hanging in the mind of survivors mainlywomen. The specter of Nari narrats the war scene where the battlefield glistened and blurred like vapor coming out of hell. The agony of widowhood and looking for their lovers are other nodal points of the research. Further, war invites violation which is very chilling issue and the performance of war is very destructive. The events are deeply felt with pain when Nari narrates the war scene in the form of spirit.